EFEKTIVITAS TERAPI WUDHU TERHADAP PENURUNAN AMARAH PADA MAHASISWA - Sagita Putri, Yansu; M.Ridho, Saputra; Berty Salsabila, Pasha; Farid, Abdanillah; Yuke, Wulandari; Siti Atiyah, Ali (CV. Doki Course and Training, 2024)
The emotion of anger is a reaction when the fulfillment of human needs and motivation is thwarted. Anger is a form of emotional expression caused by the influence of the surrounding environment. Students who are in an uncertain, unstable and explosive emotional state, where this emotional state makes it easier for students to feel angry when they are faced with a threatening situation. In fact, anger has the potential to be negative in developing emotional, physical, behavioral, educational and social aspects. One of the appropriate treatments for reducing anger in students is ablution therapy. Ablution therapy can clear the mind, soothe the heart, reduce stress, worry, anger, and can stimulate the nervous system. This research aims to determine the effectiveness of ablution therapy in reducing anger in students. This research use desciptive qualitative approach. The subject of this research was one active student. by collecting data using interview and observation methods.